Avaliação do potencial fitoquímico das folhas de Eucalyptus tereticornis Smith (myrtaceae) do semiárido nordestino ocorrente no Ceará - Castro, Marina Arruda de (2020)
The main species of eucalyptus producing 1,8-cineol (eucalyptol), unique in the Northeast, especially in Ceará, is the Eucalyptus tereticornis Smith, introduced in the Farmácias Vivas Program because it is well adapted to the conditions of the region, and for its balsamic conditions, expectorant and antiseptic airway. Thus, it started to be used as a medicine in place of the Eucalyptus globulus of the Pharmacopoeias. Another species of eucalyptus adapted to the climate of the Caatinga is Corymbia citriodora, widely used by medicinal communities, but the species is presented in its citronal leaves and for this reason it is not indicated as medicinal. Thus, the present study aimed to evaluate the phytochemical potential of Eucalyptus tereticornis Smith leaves. (Myrtaceae) from the northeastern semi-arid occurring in Ceará. Therefore, collect as fresh leaves of E. tereticornis affected in the macro-region of FortalezaCE. Preliminary studies were carried out: phytochemical approach, determination of loss on desiccation and total ash content. Extraction and analysis of essential oil, interpretation and identification of compounds. Analysis of chromatograms and mass spectra present in the scientific collection of professor Francisco José de Abreu Matos. Preparation and analysis of the fluid extract. A phytochemical approach demonstrated the presence of secondary metabolites such as: coumarins, flavonoids, saponins and tannins. The essential oils have 1,8- cineol as the major compound, in addition, the following compounds were used: α-pinene, βpinene, ρ-cymene, limonene, γ-terpinene, α-terpineol and aromadendrene, as indicated in scientific collection of professor Matos. The highest 1,8-cineole content found was in the rainy collection season in Maracanaú. CEDEFAM leaves had a low 1,8-cineole content. The scientific collection contains 24 analyzes of eucalyptus, 4 in E. tereticornis. The fluid extract showed 76.8 µL/mL of 1.8-cineole (7.68%) used as an active chemical marker and 61.71 µg/mL of coumarin (0.66 x 10-2%) analytical marker. Conclude which percentage of 1,8-cineole of essential oil in some of the studied accessions is compatible with the Brazilian Pharmacopoeia. The age of the trees, the season (rainy and dry season) and the time of collection can directly interfere with the 1,8-cineole content. The profile of the E. tereticornis matrix plant located at HPMATOS-UFC has been maintained since 1994. The fluid extract is very promising for use in herbal medicines. E. tereticornis has the potential to be included in the Brazilian Pharmacopoeia.